Estudio documental de la moneda castellana de juana la loca fabricada en los países bajos (1505-1506) - Francisco Olmos, José María de (Revista General de Información y Documentación, 2002)
This article studies the numismatic document used as a medium for political propaganda by Felipe el Hermoso in the power struggle in Castille upon the death of Isabel la Católica and reaffirms the monarch’s exclusive prerogative in the minting of coinage.